Stone Tools in Transition: From Hunter-Gatherers to Farming Societies in the Near East - Borrell, Ferran (Servei de Publicacions de la Universitat Autònoma de Barcelona, 2014)
This volume compiles the papers presented at the seventh edition of the Conference on PPN Chipped and Ground Stone Industries of the Fertile Crescent, held in Barcelona from 14 to 17 February 2012. This series of conferences/workshops started nineteen years ago - the first meeting was organised in Berlin in 1993 - and is devoted to the study of the lithic record in the Pre-Pottery Neolithic of the Near East and neighbouring regions. The seventh of these conferences was organised by the Institució Milà i Fontanals (Consejo Superior de Investigaciones Científicas) and the Prehistory Department (Universitat Autònoma de Barcelona). This volume includes a total number of 36 articles, covering a wide range of topics and disciplines related to lithic studies in the Levant over a long chronological time span (from the final stages of the Epipalaeolithic/Natufian to the Halaf period). The publication of the conference proceedings is thus an interesting synthesis of the current state of lithic studies on the Pre-Pottery Neolithic of the Near East, and consolidates this specific series of conferences as a key tool to maintain and stimulate the vitality of high quality research into the Near Eastern lithic record.